If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -20) = (3x + -10) Reorder the terms: (-20 + 2x) = (3x + -10) Remove parenthesis around (-20 + 2x) -20 + 2x = (3x + -10) Reorder the terms: -20 + 2x = (-10 + 3x) Remove parenthesis around (-10 + 3x) -20 + 2x = -10 + 3x Solving -20 + 2x = -10 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -20 + 2x + -3x = -10 + 3x + -3x Combine like terms: 2x + -3x = -1x -20 + -1x = -10 + 3x + -3x Combine like terms: 3x + -3x = 0 -20 + -1x = -10 + 0 -20 + -1x = -10 Add '20' to each side of the equation. -20 + 20 + -1x = -10 + 20 Combine like terms: -20 + 20 = 0 0 + -1x = -10 + 20 -1x = -10 + 20 Combine like terms: -10 + 20 = 10 -1x = 10 Divide each side by '-1'. x = -10 Simplifying x = -10
| 15=12x^2+24x | | 4d+8-2d=6d-10 | | -12x+2y=x+2 | | 7xy-4xy+2xy+6xy+3xy-7xy= | | 14x-(3x-7)=40 | | f(n)=2*f(n-1) | | 3(3z+1)-8=40 | | -1440=-15(-15x-29) | | 8u-1=8 | | (6+k)+12=23 | | 3(2x-7)-4(x-1)= | | 2h+10=66 | | 2h+10=66 | | y-8+124=180 | | -41=5x+9 | | -1440=-15(-15x-21) | | 1.4a+10=17 | | 6x+13=5x | | n+36=5m | | (X-3)(x+4)=x^2-5x+20 | | 9+2z-8=7z+7-4z | | a(-12)=b | | 0.6x-0.33=1 | | 4000=5.5x-460.5 | | x+16=2x-16 | | v=3.141592654(36)(16) | | 8(t-3)+4=4(3t+5)-9 | | 3x^2+7x-11=17-10x | | v=3.141592654(36)2(16) | | y-63x-3=0 | | 5.8a+14=66.2 | | 0.6-5x=2 |